Nanoparticle-Induced Phenomena in Polyurethanes - Patel D.K.; Biswas A.; Maiti P. (My University, 2025)
This chapter describes the influence of different types of nanoparticles such as metals, metal oxides, ceramics, natural clay, various forms of carbon, and zeolites on the properties of polyurethanes with special emphasis on the dimensionality of the nanoparticles. First, classification of the nanoparticles is made with typical examples. Distribution of the particles in polyurethane matrix and their interaction with the polymer chain alter the morphology of polyurethane both at the surface and in the bulk, which in turn is responsible for the dramatic changes in the properties of the composites. Organic modification on the surface of the nanoparticles makes significant changes to the overall properties of the composites. Self-assembly phenomena in polyurethanes are illustrated where hydrogen bonded molecular layers stack together forming bigger clusters observable in an optical microscope. The impact of layer by layer self-assembly on drug delivery and other properties is discussed. Improvements in the thermal and mechanical properties and flame retardancy of the composites with different types of nanoparticles are presented in detail with examples. Polyurethanes are widely used in biomedical fields and the present chapter elaborates the effectiveness of the composites toward biocompatibility including in vivo use visá-vis pure polyurethanes. It is suggested that polyurethane nanocomposites have great potential in biomedical applications. © 2016 Elsevier Ltd. All rights reserved.